PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN IPA PADA SISWA KELAS IV SDN 1 PANJER TAHUN AJARAN 2014/1015 - Wardani, Ary (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: Application of Problem Based Learning Model with Concrete Media in Natural Science Learning Improvement for the 4th Grade Students in SDN 1 Panjer Academic Year 2014/2015. The objectives of this research are to improve learning of science on the 4th grade student. This research is a Collaborative Classroom Action Research conducted for 3 cycles with the phases of planning, action, observation, and reflection. The subjects of research were 4th grade students of SDN 1 Panjer amounting to 28 students. Data collection techniques such as observation, interviews, and testing. The validity of the data used the triangulation of sources and technique. The analysis of data consisting of data reduction, data description, and conclusion. The conclusion of this research is the using of the Problem Based Learning models with concrete media can improve the learning of science for 4th grade students in SDN 1 Panjer. Keyword: Problem Based Learning, Concrete Media, Natural Science Abstrak : Penerapan Model Problem Based Learning dengan Media Konkret dalam Peningkatan Pembelajaran IPA pada Siswa Kelas IV SDN 1 Panjer Tahun Ajaran 2014/2015. Tujuan penelitian ini untuk meningkatkan pembelajaran IPA tentang sumber daya alam pada siswa kelas IV. Penelitian ini merupakan Penelitian Tindakan Kelas Kolaboratif dengan tahapan perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian adalah siswa kelas IV SDN 1 Panjer yang berjumlah 28 siswa. Teknik pengumpulan data berupa observasi, wawancara, dan tes. Validitas data menggunakan triangulasi sumber dan teknik. Analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Kesimpulan penelitian ini adalah penggunaan model Problem Based Learning dengan media konkret dapat meningkatkan pembelajaran IPA pada siswa kelas IV SDN 1 Panjer. Kata Kunci: Problem Based Learning, Media Konkret, IPA